Anticipation effects of protectionist U.S. trade policies - Norbert Metiu (Deutsche Bundesbank, 2020)
This paper investigates the international spillover effects of U.S. trade protection. Using micro-level data on anti-dumping, countervailing duties, and safeguards, I develop a new measure of U.S. trade policy announcement shocks for the period 1988-2015 that is free of confounding factors. Estimates using the new measure indicate that announced, but not yet imposed, U.S. trade restrictions give rise to contractions in major trading partners' output and investment. Counterfactual results indicate that a decline in business confidence accounts for the lion's share of these anticipation effects. A narrative analysis that quantifies the extent of newspaper coverage of U.S. trade protection shows that media attention facilitates the propagation of protectionist shocks. The results are consistent with an expectations channel of trade policy.
Keywords: E32; F13; 330; Anticipation Effects; Business Cycles; Announcement Shocks; Protectionism; Trade